AI-3 Synthesis Is Not Dependent on luxS in Escherichia coli - Walters, Matthew (American Society for Microbiology, 2006)
The quorum-sensing (QS) signal autoinducer-2 (AI-2) has been proposed to promote interspecies signaling in a broad range of bacterial species. AI-2 is spontaneously derived from 4,5-dihydroxy-2,3-pentanedione that, along with homocysteine, is produced by cleavage of S-adenosylhomocysteine (SAH) and S-ribosylhomocysteine by the Pfs and LuxS enzymes. Numerous phenotypes have been attributed to AI-2 QS signaling using luxS mutants. We have previously reported that the luxS mutation also affects the synthesis of the AI-3 autoinducer that activates enterohemorrhagic Escherichia coli virulence genes. Here we show that several species of bacteria synthesize AI-3, suggesting a possible role in interspecies bacterial communication. The luxS mutation leaves the cell with only one pathway, involving oxaloacetate and l-glutamate, for de novo synthesis of homocysteine. The exclusive use of this pathway for homocysteine production appears to alter metabolism in the luxS mutant, leading to decreased levels of AI-3. The addition of aspartate and expression of an aromatic amino acid transporter, as well as a tyrosine-specific transporter, restored AI-3-dependent phenotypes in an luxS mutant. The defect in AI-3 production, but not in AI-2 production, in the luxS mutant was restored by expressing the Pseudomonas aeruginosa S-adenosylhomocysteine hydrolase that synthesizes homocysteine directly from SAH. Furthermore, phenotype microarrays revealed that the luxS mutation caused numerous metabolic deficiencies, while AI-3 signaling had little effect on metabolism. This study examines how AI-3 production is affected by the luxS mutation and explores the roles of the LuxS/AI-2 system in metabolism and QS.